MODIFICATION OF THE INDONESIAN GROWING BUCKET COVER DESIGN ON THE THICKNESS OF THE PIPE PLACE TO REDUCE WARPAGE USING SOLIDWORKS PLASTICS SOFTWARE - Kurniawan, Perwita; Suprabo, Cornelius Tyas Lintang; Silvaro, Stefanus Bima; Hutama, Adhi Setya (Department of Mechanical Engineering Education, 2024)
Cover Indonesian Growing Bucket has a product defect problem in the form of a warpage caused by a design considered good. There was a discrepancy in the parameter settings with the initial analysis results, resulting in a difference in cooling time of 2.3 s from the original 3.9 s. This happened because parameter changes aimed to reduce warpage cycle time from the original 25.4 s to 23.8 s. Based on the problems, design modifications and analysis were carried out using Solidworks Plastics software. The design modification and analysis process was carried out using the Experiment of Analysis method, which was carried out by modifying the thickness of the part, which resulted in a warpage. The analysis was carried out to obtain optimal thickness results with the smallest cooling time gap. Modifications and design analysis are done by making three (3) alternative thicknesses for the pipe clamp section. The best modification of the three (3) alternatives made will be used as a reference basis for making material cost calculation data. From the results of design modifications and analysis, it was found that the design thickness changed to 1.5 mm. Based on the results of this analysis, alternative options are produced, which are then used as a reference in design modifications so that the resulting fill time and cycle time are more optimal.